Recalcitrant infection following total knee arthroplasty: a report of two cases - Zainol Fithri, Zairul Nizam; Badaruddin, Badrul Shah (Asia Pacific Orthopaedic Association, 2006)
Infection following total knee arthroplasty can be devastating. Even with established treatment protocols, eradication of the infection may not be feasible. We report 2 patients who required above-knee amputation to eradicate recalcitrant infection.